Does death penalty have a deterrent effect on homicides? - Du, Shangzhu (2015)
Death penalty has been practiced by most societies in the past but a growing number of countries have abolished this sanction. Among all debates about whether to retain or abolish death penalty, the effect of death penalty on deterring homicides is the most controversial arguing point. This paper aims at examining the significance of deterrent effects of death penalty, taking into consideration country-specific economic climates, in order to provide policy makers with meaningful insights so as to make better-informed decisions. In this paper, we employ detailed information of death penalty and its executions in 50 U.S. states and 49 other countries in years 1995-2012 to conduct OLS and 2SLS regression analysis. Besides, we also explore whether the strength of the deterrent effect varies with economic factors, through adding in interaction of death penalty with GDP per capita and unemployment rate and subsequently suitable groupings. The results of OLS panel data and 2SLS regression consistently return insignificant deterrent effect of death penalty on homicide rates. Further investigations reveal that death penalty is more effective in deterring homicides in countries with poor economic conditions, indicated by lower per capita GDP and higher unemployment rate.